Pengawasan Mahasiswa Bidikmisi di Universitas Negeri Padang - Sri Okto Berta; Dasman Lanin; Adil Mubarak (Jurnal Teori dan Riset Administrasi Publik, 2018)
This study discusses the supervision of Bidikmisi students at Padang State University. The purpose of this study is to describe the supervision of Bidikmisi students, obstacles and efforts in supervising Bidikmisi students at Padang State University. This type of research is descriptive qualitative research. The research location is at Padang State University. Primary data is data obtained from interviews and observations, while secondary data is data obtained from documentation studies. The informants in this study were the Head of BAK UNP, UNP Student Affairs Department, Deputy Dean III FIS, FT and FBS, and several Bidikmisi recipient students. Based on the results of the study, it can be concluded as follows: First, the supervision carried out by UNP on Bidikmisi students at UNP is good but not optimal, supervision is done preventively and repressively. Preventive through socialization and training, Repressive through guidance and even revocation of Bidikmisi. Second, the constraints faced by Padang State University are internal constraints, namely the lack of a survey team that causes a tendency to inaccurate Bidikmisi targets, the next obstacle is the commitment and seriousness of Bidikmisi students in fulfilling their duties and obligations as Bidikmisi students. Third, efforts made to overcome these obstacles are by optimizing guidance through socialization, training and guidance for Bidikmisi students.